2019
DOI: 10.1007/s11523-019-00656-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Drug-induced Interstitial Lung Disease in Advanced Breast Cancer Patients Receiving Everolimus Plus Exemestane

Abstract: Background Everolimus-related interstitial lung disease (ILD) (also: pneumonitis) poses a difficulty for physicians, as it is hard to discriminate ILD from other causes of respiratory symptoms and to decide on safe treatment continuation. Objective We investigated the capability of pulmonary function tests (PFT), plasma biomarkers, everolimus pharmacokinetics, and FDG-PET to discriminate between everolimus-related ILD and other causes of respiratory problems and to predict the severity of ILD. Patients and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…We also found that the average C trough at steady state did not differ between patients with and without any grade of pneumonitis. This observation is consistent with those in earlier studies demonstrating no correlation between everolimus C trough and the occurrence of pneumonitis [30,31]. Therefore, monitoring of blood everolimus concentrations may not help identify patients at increased risk of pneumonitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that the average C trough at steady state did not differ between patients with and without any grade of pneumonitis. This observation is consistent with those in earlier studies demonstrating no correlation between everolimus C trough and the occurrence of pneumonitis [30,31]. Therefore, monitoring of blood everolimus concentrations may not help identify patients at increased risk of pneumonitis.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, monitoring of blood everolimus concentrations may not help identify patients at increased risk of pneumonitis. Further development of reliable biomarkers in addition to serum KL-6 levels is necessary to improve the prediction of mTOR inhibitor-induced pneumonitis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The main thoracic toxicity of everolimus is pneumonitis. 6 However, nonspecific pleuritis has been associated with everolimus, 7 while chylothorax has been described in a cardiac transplant treated with everolimus. 8 In the described patient, disease progression was proved by pleural puncture and pathological involvement and was accompanied by CA 15-3 increase.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mechanism of uptake of 18F-Fluorodeoxyglucose (18F-FDG) is shared by neoplastic cells and inflammatory cells, false positive results interpreted as of oncological significance are frequently caused by underlying infections instead. Therefore, during several antineoplastic treatments, drug-related pneumonitis of any form may be erroneously interpreted as progressive disease by 18F-FDG PET/CT [ 140 , 141 , 142 , 143 , 144 ]. To date, this represents a hard to solve diagnostic dilemma, at least on the basis of the conventional image qualitative analysis.…”
Section: Diagnosis and Therapymentioning
confidence: 99%